Two new species of Opeatocerata Melander (Diptera, Empididae, Empidinae) from the Brazilian Amazon Basin - Câmara, J. T.; Rafael, J. A. (Zootaxa, 2011)
Two new species of the Neotropical genus of Empidinae, Opeatocerata: O. trilobata sp. nov. and O. melanderi sp. nov., are described and illustrated from Manaus. This is the first record of the genus from Brazilian Amazonia.